Factors related to the loss of follow-up in pregnant women with syphilis: an integrative review - Paula Lima da Silva; Marli Teresinha Gimeniz Galvão; Emanoelle Fernandes Silva; Braulio Vieira de Sousa Borges; Jefferson Abraão Caetano Lira; Rosilane de Lima Brito Magalhães (Rev Rene)
Objective: to analyze factors related to the loss of follow-up in pregnant women with syphilis. Methods: Integrative review developed in six databases. The PICo strategy was used to elaborate the guiding question and select the descriptors and keywords through Boolean operators. 20 articles were included in the final sample. Results: the factors related to the loss of follow-up in pregnant women with syphilis were: age; schooling; diagnosis and late onset of treatment; prenatal failure and low adherence of the partner to treatment. In addition, the lack of knowledge of professionals about the management of syphilis and the failures in counseling were found to be factors inherent to the loss of follow-up. Conclusion: pregnant women under 20, low schooling, stigma, fear, non-treatment of partnership, inadequate treatment and lack of professional training and guidance to pregnant women were associated with the loss of follow-up of pregnant women with syphilis.